ANALISIS PENDAPATAN DAN KELAYAKAN USAHATANIPADI SAWAH DI DESA SIENJO KECAMATAN TORIBULU KABUPATEN PARIGI MOUTONG - Nursyafa’ah, Nursyafa’ah; Rauf, Rustam Abd.; Hadayani, Hadayani (AGROTEKBIS, 2018)
Central Sulawesi is one of Indonesias rice-producing areas potentially to be developed due to its vast area and abundant resources.The purpose ofthis research was to determine the income and feasibility of wetland rice farming system in Sienjo village Toribulu sub district of Parigi Moutong district. The number of samples of 31 respondents was drawn from a population of 102 farmers using a simple random sampling technique.The average revenue generated by the farmers was IDR 17,400,768/1.03 ha/planting season (PS) or IDR. 16,856,992/ha/PS with an average cost ofIDR. 8.797.013/1.03ha/PS or 8.540.790/ha/PS, therefore the average income was IDR 8,603,760/1.03ha/PS or IDR. 8.334.892/ha/PS. The feasibility value ofthe wetland farming system in Sienjo village Toribulu subdistrict of Parigi Moutongdistrict was 1.98 indicating that any expenditure of IDR 100 will generate revenue of IDR 198. Thus, thewetland rice farming in the Village of Sienjo is feasible to be developed. Keywords:Feasibility, Income, Wetland rice farming.